Polyethylene/synthetic boehmite alumina nanocomposites: Structure, thermal and rheological properties (eXPRESS Polymer Letters, 2010)
Synthetic boehmite alumina (BA) has been incorporated up to 8 wt% in low density polyethylene (LDPE) and high density polyethylene (HDPE), respectively, by melt compounding. The primary nominal particle size of these two BA grades was 40 and 60 nm, respectively. The dispersion of the BA in polyethylene (PE) matrices was investigated by scanning and transmission electron microscopy techniques (SEM and TEM). The thermal (melting and crystallization), thermooxidative (oxidation induction temperature and time), and rheological behaviors of the nanocomposites were determined. It was found that BA is nanoscale dispersed in both LDPE and HDPE without any surface treatment and additional polymeric compatibilizer. BA practically did not influence the thermal (melting and crystallization) and rheological properties of the parent PEs. On the other hand, BA worked as a powerful thermooxidative stabilizer for LDPE, and especially for HDPE nanocomposites.